2012
DOI: 10.1016/j.bbmt.2011.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Highly Variable Pharmacokinetics of Once-Daily Intravenous Busulfan When Combined with Fludarabine in Pediatric Patients: Phase I Clinical Study for Determination of Optimal Once-Daily Busulfan Dose Using Pharmacokinetic Modeling

Abstract: Busulfan has a narrow therapeutic range, and in children, pharmacokinetic variability has been found to be high even after the use of intravenous (i.v.) busulfan. Recently, a reduced toxicity myeloablative regimen showed promising results, but the data of busulfan pharmacokinetics in hematopoietic stem cell transplantation (HSCT) using a targeted busulfan/fludarabine regimen in children has not yet been reported. We performed therapeutic drug monitoring (TDM) after once-daily i.v. busulfan combined with fludar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 41 publications
3
53
2
Order By: Relevance
“…As a result, there is a large interpatient variability in busulfan clearance. Lee et al [24] observed clearance rates from 1.74 to 6.94 mL/min/kg after administration of a oncedaily dose of 120 mg/m 2 in 23 children aged .9 to 18.1 years (median, 9.3 years). This was echoed by Nath et al [25], who observed a coefficient of variation of 35% in the clearance of busulfan in 40 children.…”
Section: Discussionmentioning
confidence: 96%
“…As a result, there is a large interpatient variability in busulfan clearance. Lee et al [24] observed clearance rates from 1.74 to 6.94 mL/min/kg after administration of a oncedaily dose of 120 mg/m 2 in 23 children aged .9 to 18.1 years (median, 9.3 years). This was echoed by Nath et al [25], who observed a coefficient of variation of 35% in the clearance of busulfan in 40 children.…”
Section: Discussionmentioning
confidence: 96%
“…While it is not possible to directly compare the results from different experimental groups because each received different treatment regimens, future studies might explore methods to improve reliability of busulfan sterilization, alternative agents (e.g., cyclophosphamide), or use of irradiation. Highly variable busulfan pharmacokinetics in human patients, even intra-individually, is well known [3841]. Therefore, although we took great care to ensure accurate busulfan dosing and employed an inbred mouse strain to reduce the influence of genetic modifiers on the experimental outcomes, differences in busulfan pharmacokinetics between individual animals could have led to the variability in busulfan efficacy we observed.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the variability of daily AUC was high, but the total AUC of the 4 days approached the target AUC. Because hepatic toxicity and VOD are associated with high total AUC level, a total target AUC <77,000 µg·hr/L was recommended to reduce the toxicity and improve the outcome of HSCT1). There was no definite HSCT-related toxicity related observed in our patient, and this may have been be assisted by busulfan dose adjustment based on TDM.…”
Section: Discussionmentioning
confidence: 76%
“…On the first day, the patient received 120 mg/m 2 of busulfan, and targeted dose of busulfan was administered on subsequent three days. The target area under curve (AUC) of busulfan was 18,500–19,000 µg·hr/L, and the target cumulative AUC of busulfan for the 4 days was 75,000 µg·hr/L1). The total cumulative AUC of busulfan that was administered over 4 days was 73,148.1 µg·hr/L, with a daily AUC of busulfan of 22,043.7 µg·hr/L, 21,250.2 µg·hr/L, 19,691.5 µg·hr/L, and 10,162.7 µg·hr/L.…”
Section: Case Reportmentioning
confidence: 99%